Struktur Aset, Profitabilitas, Likuiditas dan Pertumbuhan Penjualan terhadap Struktur Modal Perusahaan Sub Sektor Otomotif dan Komponen yang Terdaftar di Bursa Efek Indonesia - Agung Himawan (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2019)
Thias reseaarch is conaducting an emapirical teasat oan tahe effeact oaf asset struacture, profitability, liquaidity anad growth of sales oan thae capital structureof industrial company automotive and component listing ian thae Inadonesia Stoack Eaxchange in 2013-2018. Tahe diffaerence waith preavious reseaarch laies in the use ofindepaendent variaables, thae taype of comapany, the nuamber oaf sampales uased anad tahe stuady paeriod. Tahis raesearch ias quanatitative. Thae analaytic metahod ian thais reseaarchias maultiple linaear regraession anaalysis. Tahe reasults oaf tahe t-teast hypothesias shoaw thaat thae aassets struacuture (AS), liquaidity, cuarrent raatio (CR) haave a signaificant eaffect oan caapital struacture, deabt to eqauity raatio (DER), whaile profiatability, reaturn oan asasets (ROA) anad growath of saales (GROaWTH) thaat haas nao signaificant effecat oan caapital astructure.